A point mutation and large deletion at the candidate avirulence locus AvrMlp7 in the poplar rust fungus correlate with poplar RMlp7 resistance breakdown - Clémentine Louet; Méline Saubin; Axelle Andrieux; Antoine Persoons; Mathilde Gorse; Jérémy Pétrowski; Bénédicte Fabre; Stéphane De Mita; Sébastien Duplessis; Pascal Frey; Fabien Halkett (Molecular Ecology, 2023)
The deployment of plant varieties carrying resistance genes ( R ) exerts strong selection pressure on pathogen populations. Rapidly evolving avirulence genes ( Avr ) allow pathogens to escape R ‐mediated plant immunity through a variety of mechanisms, leading to virulence. The poplar rust fungus Melampsora larici ‐ populina is a damaging pathogen of poplars in Europe. It underwent a major adaptive event in 1994, with the breakdown of the poplar RMlp7 resistance gene. Population genomics studies identified a locus in the genome of M . larici ‐ populina that probably corresponds to the candidate avirulence gene AvrMlp7 . Here, to further characterize this effector, we used a population genetics approach on a comprehensive set of 281 individuals recovered throughout a 28‐year period encompassing the resistance breakdown event. Using two dedicated molecular tools, genotyping at the candidate locus highlighted two different alterations of a predominant allele found mainly before the resistance breakdown: a nonsynonymous mutation and a complete deletion of this locus. This results in six diploid genotypes: three genotypes related to the avirulent phenotype and three related to the virulent phenotype. The temporal survey of the candidate locus revealed that both alterations were found in association during the resistance breakdown event. They pre‐existed before the breakdown in a heterozygous state with the predominant allele cited above. Altogether, these results suggest that the association of both alterations at the candidate locus AvrMlp7 drove the poplar rust adaptation to RMlp7 ‐mediated immunity. This study demonstrates for the first time a case of adaptation from standing genetic variation in rust fungi during a qualitative resistance breakdown.

Long‐term influence of early human occupations on current forests of the Guiana Shield - Guillaume Odonne; Martijn van den Bel; Maxime Burst; Olivier Brunaux; Miléna Bruno; Etienne Dambrine; Damien Davy; Mathilde Desprez; Julien Engel; Bruno Ferry; Vincent Freycon; Pierre Grenand; et al. (Ecology, 2019)
To decipher the long‐term influences of pre‐Columbian land occupations on contemporary forest structure, diversity, and functioning in Amazonia, most of the previous research focused on the alluvial plains of the major rivers of the Amazon basin. Terra firme, that is, nonflooded forests, particularly from the Guiana Shield, are yet to be explored. In this study, we aim to give new insights into the subtle traces of pre‐Columbian influences on present‐day forests given the archaeological context of terra firme forests of the Guiana Shield. Following archaeological prospects on 13 sites in French Guiana, we carried out forest inventories inside and outside archaeological sites and assessed the potential pre‐Columbian use of the sampled tree species using an original ethnobotanical database of the Guiana Shield region. Aboveground biomass (320 and 380 T/ha, respectively), basal area (25–30 and 30–35 m 2 /ha, respectively), and tree density (550 and 700 stem/ha, respectively) were all significantly lower on anthropized plots (As) than on nonanthropized plots ( NA s). Ancient human presence shaped the species composition of the sampled forests with Arecaceae, Burseraceae, and Lauraceae significantly more frequent in As and Annonaceae and Lecythidaceae more frequent in NA s. Although alpha diversity was not different between As and NA s, the presence of pre‐Columbian sites enhances significantly the forest beta diversity at the landscape level. Finally, trees with edible fruits are positively associated with pre‐Columbian sites, whereas trees used for construction or for their bark are negatively associated with pre‐Columbian sites. Half a millennium after their abandonment, former occupied places from the inner Guiana Shield still bear noticeable differences with nonanthropized places. Considering the lack of data concerning archaeology of terra firme Amazonian forests, our results suggest that pre‐Columbian influences on the structure (lower current biomass), diversity (higher beta diversity), and composition (linked to the past human tree uses) of current Amazonian forests might be more important than previously thought.